James and the Megan Family: Navigating Court and Allegations of Abuse. (July 2020) - Hendricks, Bret; Ordway, Ann; Bradley, Loretta; Noble, Nicole
Couples and family counselors daily encounter ethical dilemmas. These dilemmas are complex and multifaceted. This article is written to discuss and provide information to couples and family counselors who seek to work ethically with clients who have been accused of abuse to minors. The authors of this article consulted an expert in ethics and standards of care related to the abuse of minors to identify ethical analysis of dilemmas through a fictional case study. The respondent to the case study provides recommendations to assist couples and family counselors as they follow the International Association of Marriage and Family Counselors Ethics Code as well as other professional ethics codes and standards of practice.